Innovation "Ginger Powder" Processing to Increase The Value of Agricultural Produce with Community Development Towards Food Security from Utilization - Thongmeethip, Kitisak; Niyomratjaroon, Arisaravan (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purpose of this study was to promote career creation and income for the community through the processing of large amounts of product (ginger) in Nam Tob Village, Pla Ba Sub-district, Phu Ruea District, Loei Province, and to promote knowledge in the dimension of food security utilization of agricultural production In Nam Tob Village, Pla Ba Sub-district, Phu Ruea District, Loei Province. The sample group in this study were 70 samples recruited with a purposive sampling method. Data collection is document research, observation and brainstorming. Research findings explores that agriculture segment is still the major career in the upper northeast region of Thailand that is consistent with the context of local lives. The popular occupation of agriculture is "planting ginger". Farmers together with the academic sector in the area have foreseen the management of ginger by processing to increase the value of ginger in the form of ginger powder as one way to create careers and income for the community and to realize the importance of food security issues as well as bringing large amounts of produce to generate income, processing (innovation) under the project to enhance the integrated sub-district economy and society (U2T) of Loei Rajabhat University.